The course of work on the Ecumenical Bible - Zalisz, Jadwiga (The Bible as a meeting place for Christian denominations, 2022)
The study presents the course of work on the Ecumenical Bible and the basic assumptions for the translation of the work. The beginning of ecumenical (or interfaith) translation initiatives is the Dogmatic Constitution on Divine Revelation of the Second Vatican Council, called Dei Verbum, of November 18, 1965. Thanks to this document, in 1968 the Guiding Principles of Interfaith Collaboration in Bible Translation were created, which are a joint document of the Secretariat for Christian Unity and the United Bible Societies. In 1987, the Guidelines for Interfaith Collaboration in Translating the Bible were published. They very precisely define which texts of the Old Testament in Hebrew and the New Testament in Greek should be used, and they also provide information on how to resolve the differences in the canon of books between the editions of Catholic and Protestant translations. Based on the aforementioned documents and the experience of the team of translators, a model of work on ecumenical translation was created. The preparation of the Ecumenical Bible took over twenty years, and a group of 70 people collaborated on its creation. The joint work resulted in the publication of the text in 2017.